Emoções e saúde mental: uma leitura de autores adventistas do século XX - Bellotti, Karina Kosicki (Revista Brasileira de História das Religiões, 2025)
Our article starts from two observations, which are also theoretical and empirical assumptions: (1) for some time now, the mental and emotional health of individuals has been a global concern (and Brazil is no different); (2) in addition to states and other public health organizations, religious communities of various beliefs, models of faith, and practices are also concerned with the matter. As a hypothesis, we understand that the Seventh-day Adventist Church (SDA), for over a century, has stood out among other Christian churches regarding the mental, emotional, and physical health of its members and others under its influence, even non-Adventists. To avoid an obvious path - namely, another reading of the texts by the prophetess Ellen G. White, which can be considered foundational to the SDA - we opted to analyze two 20th-century Adventist authors concerned with mental and emotional health: Humberto O. Swartout and Marcelo I. Fayard. Through documentary (sources) and bibliographic(commentaries) research, our methodology is based on both the history of emotions and the sociology of religious emotions. Among the results achieved, we highlight that Adventist books on mental and emotional health have always aimed to reach the internal Adventist community but to serve as a calling card for non-Adventists in each nation, primarily through colportage (book ministry).